Getting to(o) easy: boosting Open Access compliance by tailoring approaches to researchers - Bryce, Michael; Brady, Kyle; Knowles, Kirsty; Proven, Jackie (My University, 2016)
Poster presented at RepoFringe 2016 by Michael Bryce, Kyle Brady, Kirsty Knowles and Jackie Proven, all of the University of St Andrews. The introduction reads: "As a small, research-intensive university with diverse subject range, we tailor our approach to match researcher expectations within Schools and Centres to meet funder requirements and the University Open Access Policy."
The map contains Ordnance Survey data © Crown copyright and database right 2010.
Keywords: Open Access